Subperiosteal Papilla Augmentation With a Non–Animal‐Derived Hyaluronic Acid Overlay Technique. Issue 1 (4th October 2019) - Spano, Stephen J.; Ghilzon, Romanita; Lam, David K.; Goldberg, Michael B.; Tenenbaum, Howard C.
Abstract : Introduction: Loss of the interdental papilla, leading to the formation of black triangular spaces just below the contact area of adjacent teeth, is one of the most challenging periodontal conditions to treat and often requires an interdisciplinary approach by the periodontist, restorative dentist, and orthodontist. Although these "black triangles" may appear quite small from a clinician's standpoint, they can have a significant impact on oral health satisfaction for patients. This case series illustrates a novel minimally invasive approach to restore interdental papilla deficiencies. Case Presentation: Four interdental papilla defects were treated in three females. No patients were lost to follow‐up over 6 months. The surgery consisted of a horizontal incision placed apical to the area of papillary loss in the alveolar mucosa just beyond the mucogingival junction. An interdental subperiosteal tissue space was then created by tunneling toward and under the dental papilla. Once adequate release was achieved, dermal filler was administered into and underneath the deficient papilla. The papillary margins were then sealed with cyanoacrylate and additional dermal filler was injected as needed to achieve ideal papillary fill. Six months after treatment there was an improvement in patient‐satisfaction regarding papilla fill demonstrated by a mean increase in visual analogue scale (VAS) measurements of 62.46%. Mean papilla fill was 1.75 mm. Conclusion: This surgical technique demonstrates the restoration of deficient interdental papillae between teeth and implants, and perhaps as importantly, a considerable improvement in patient‐based outcomes quantified through VASs.